Damned If She Does, Damned If She Doesn’t: De-Legitimization of Women’s Agency in Commonwealth v. Woodward - Karlin, Molly (Columbia Journal of Gender and Law, 2008)
When Deborah Eappen left for work on the morning of February 4, 1997, her eight-month-old child, Matthew, was alive and in the care of his au pair of three months, British nineteen-year-old Louise Woodward. When she next saw Matthew, he was in the hospital, the victim of severe head trauma. Five days later he was dead. The death of a child is always a disturbing event and a manifest injustice. Even where an objective analysis would fail to find fault, the tragic nature of the occurrence will lead to a search for blame. This phenomenon is intensified in the courtroom, as the adversarial process demands the placement of blame. Yet how blame is dispersed is often informed by far more than the evidence put before the jury. Although the parties before the court may not so acknowledge, deep-seated social understandings can also play a role in the distribution of blame. The trial that ensued from the death of Matthew Eappen was no exception. This Article will evaluate many of the social and legal factors that influence the distribution of blame when a child dies. It proceeds on the assumption that the standards of criminal law are intended in part to align legal culpability with causation-that is, the defendant’s proximal responsibility for the occurrence of the act. Specifically, this Article explores the disparate social criticism and legal treatment of infanticidal mothers as compared with other caretakers who kill, and concludes that, in affording non-mothers “excuses” that are not permitted for mothers, both society and courts have disregarded traditional standards required for murder and manslaughter convictions, such as proof of intent and knowledge per that of the reasonable person. As a result, when faced with a female defendant charged with killing a child in her care, both the public and the legal system fail to give proper regard to the defendant’s choices, and thus fail to accord her the appropriate level of blame. Furthermore, the objectification of the female defendant, particularly when she is a mother, as a symbol for a large subset of women may deny her the ability to explain her own story in the courtroom. I have referred to these effects-the tendency to ignore the actual responsibility of a particular defendant in light of a pervasive cultural countemarrative and the application of different standards of culpability to different groups of women-as the “de- legitimization of women’s agency.”